A Physical Fitness Coaching Clinic for Physical Education Teachers in Kapuas Hulu District - Stephani Yane; Rio, Rio Wardhani; Iskandar; Awang Roni Effendi; Heri Rustanto; Yenni Rizal (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Abstract Physical education is a discipline that studies health, physical development, and student skills through sports activities. PJOK (Physical Education, Sports, and Health) teachers play an important role in the physical education system. In addition to teaching, they are responsible for educating students about health and physical fitness. To improve the competence of PJOK teachers to become professionals with the hope of enhancing the quality of learning, a physical fitness coaching clinic was conducted for PJOK teachers in Kapuas Hulu Regency. The procedures carried out included the distribution of a pre-test questionnaire to assess understanding of physical fitness, in-depth material sessions, practical measurement of physical fitness, and the distribution of a post-test questionnaire to evaluate the results of the activities. This program was attended by PJOK teachers from junior high schools (SMP), senior high schools (SMA), and vocational schools (SMK) throughout Kapuas Hulu Regency.